S122 Outcome After Pulmonary Endarterectomy (pea): Long Term Follow-up Of The Uk National Cohort. (10th November 2014) - Cannon, J; Su, L; Page, K; Ponnaberanam, A; Toshner, M; Taboada, D; Sheares, K; Ng, C; Dunning, J; Tsui, S; Jenkins, D; Pepke-Zaba, J
Abstract : Introduction: Chronic thromboembolic pulmonary hypertension (CTEPH) is a life threatening condition that historically has a poor outcome with supportive medical treatment. Pulmonary endarterectomy (PEA) is the treatment of choice and offers the only chance of cure. Data on the predictors of long term survival after PEA are limited. We analysed the long-term data from the UK PEA cohort. Method: All patients who underwent a PEA for CTEPH at Papworth hospital between January 1997 and December 2012 were included. Pre- and post-operative data on haemodynamics, exercise capacity, functional class and targeted PAH therapies taken were obtained from databases of the UK PH centres. The NHS spine summary care record tracking system was used for survival data and causes of death from the England and Scotland General Register Offices. The causes of death were further classified into 4 groups: 1. Post operative, 2. Right ventricular failure away from operative period, 3. Related to anticoagulation, 4. Unrelated to CTEPH e.g. malignancy. Results: 880 patients underwent PEA over the 15 year period. The mean age was 57 (range 15–84) and 53% were male. 89% were in WHO functional class 3 or 4 before surgery with an mean mPAP of 47 mmHg and PVR of 830 dynes. Post surgery 84% of patients were in WHO functional class 1 or 2 and there was a reduction in the mean mPAP to 27 ± 9 mmHg and PVR to 286 ± 198 dynes/sec/cm 5 by 12 months (p). Conclusion: There was prolonged haemodynamic improvement but targeted therapy was used in 23% of patients with a mean follow-up of 4.3 years. The 10-year survival was 72% with mortality predominantly in the peri-operative period and later due to causes unrelated to CTEPH.